From the 1990s Onwards: Activist and Artivist Practices – the Case of Croatia - Marjanić, Suzana (Poznańskie Studia Slawistyczne, 2019)
The article documents the relation of performance art, actions, interventions, happenings, and the democracy of capital for the ruling power through double optics. The first optics constitutes a niche within which art is treated as a crime, as in the case of e.g. the individual guerrilla action Black Peristyle (Crni Peristil) from 1998, the author of which was summoned for interrogation at the Department for Terrorism and War Crimes. The second optics constitutes a niche within the framework of which art engagingly views what is political, what is criminal, what is taking place in this Balkan planetarium of ours – thus demonstrating that personal is (indeed) political – on the example of the independent scene on the one hand (Močvara Club and ATTACK!; I only address the independent scene of Zagreb on this occasion), but also the concept of “Green Democracy” (whereby I used the syntagma by Vandana Shiva) on the example of the activist practice of Animal Friends, as well as the examples of the artistic practice of multimedia artist Ivan Mesek, who also sought to indicate the suffering of animals on the barbed wire (Hungarian-Croatian and Slovenian-Croatian borders). With the aforementioned examples from the niche of animal rights, I sought to document the refugee crisis on the Balkan Route through the optics of equalising speciesism (species-based discrimination) and racism.